MOF-derived porous NiO-Co3O4 for high performance ultrafast pulse generation. (November 2022) - Zhang, Yani; Song, Zhuoying; Li, Xiaohui; An, Mingqi; Han, Yueheng; Chen, Enci; Hu, Jiyi; Huang, Xiangzhen; Li, Gang; Lu, Hongbing
Highlights: The nonlinear optical properties of metal–organic framework derivatives porous NiO-Co3 O4 were investigated for the first time. For the first time, traditional soliton ultrafast pulse output was realized in an erbium-doped fiber laser (EDFL) by using the metal–organic framework derivative porous NiO-Co3 O4 as a SA. For the first time, dual-wavelength mode locking has been achieved in an EDFL by using the metal–organic framework derivative porous NiO-Co3 O4 as a SA. Harmonic mode locking up to 1.04 GHz (corresponding to the 211th harmonic pulse) is achieved for the first time in an EDFL by using metal–organic framework derivative porous NiO-Co3 O4 as a SA. Abstract: Porous NiO-Co3 O4 architectures, as one kind of novel metal organic frameworks (MOFs), have attracted extensive attention in the field of electrocatalysis and optoelectronics thanks to its large specific surface area, porous and adjustable pore size, structural and functional diversity. Although MOFs have made great achievements in many fields, the research on their ultrafast photonics fields is still in its infancy. Therefore, in this paper, NiO-Co3 O4 polyhedra were synthesized by using zeolitic imidazolate framework (ZIF-67) as the metal source and sacrificial template. In addition, combining NiO-Co3 O4 polyhedra with the microstructure fiber, nonlinear optical (NLO) absorption of the saturable absorber (SA) structure was characterized by two arm measurement technique. The experimental determination of the saturable intensity and modulation depth of NiO-Co3 O4 polyhedra were 9.1 MW/cm 2 and 5.6%, which indicates that NiO-Co3 O4 polyhedra possess excellent NLO absorption properties. Here, for the first time, it is proved that NiO-Co3 O4 polyhedra can be served as an efficient SA to readily generate dual-wavelength mode-locking and high repetition rate output pulses up to 1.04 GHz (corresponding to 211th harmonic pulse) in erbium-doped fiber laser (EDFL), which is much higher than previous research results based on MOFs and their derivatives as SAs for ultrafast photonics. These experimental results demonstrate that the NiO-Co3 O4 polyhedra SA derived from ZIF-67 is a new star which plays an important role in the field of ultrafast photonics.